Adoptive T Cell Therapy Targeting Different Gene Products Reveals Diverse and Context-Dependent Immune Evasion in Melanoma - Effern, Maike; Glodde, Nicole; Braun, Matthias; Liebing, Jana; Boll, Helena N; Yong, Michelle; Bawden, Emma; Hinze, Daniel; van den Boorn-Konijnenberg, Debby; Daoud, Mila; Aymans, Pia; Landsberg, Jennifer; et al. (Immunity (Cambridge, Mass.), 2020)
Tumor immune escape limits durable responses to T cell therapy. Here, we examined how regulation and function of gene products that provide the target epitopes for CD8 T cell anti-tumor immunity influence therapeutic efficacy and resistance. We used a CRISPR-Cas9-based method (CRISPitope) in syngeneic melanoma models to fuse the same model CD8 T cell epitope to the C-termini of different endogenous gene products. Targeting melanosomal proteins or oncogenic CDK4 (Cyclin-dependent kinase 4) by adoptive cell transfer (ACT) of the same epitope-specific CD8 T cells revealed diverse genetic and non-genetic immune escape mechanisms. ACT directed against melanosomal proteins, but not CDK4 , promoted melanoma dedifferentiation, and increased myeloid cell infiltration. CDK4 antigen persistence was associated with an interferon-high and T-cell-rich tumor microenvironment, allowing for immune checkpoint inhibition as salvage therapy. Thus, the choice of target antigen determines the phenotype and immune contexture of recurrent melanomas, with implications to the design of cancer immunotherapies.